Fertility preservation for women with breast cancer: a multicentre randomized controlled trial on various ovarian stimulation protocols. Issue 8 (1st July 2022) - Balkenende, Eva M E; Dahhan, Taghride; Beerendonk, Catharina C M; Fleischer, Kathrin; Stoop, Dominic; Bos, Annelies M E; Lambalk, Cornelis B; Schats, Roel; Smeenk, Jesper M J; Louwé, Leonie A; Cantineau, Astrid E P; de Bruin, Jan Peter; et al.
Abstract: STUDY QUESTION: Does ovarian stimulation with the addition of tamoxifen or letrozole affect the number of cumulus-oocyte complexes (COCs) retrieved compared to standard ovarian stimulation in women with breast cancer who undergo fertility preservation? SUMMARY ANSWER: Alternative ovarian stimulation protocols with tamoxifen or letrozole did not affect the number of COCs retrieved at follicle aspiration in women with breast cancer. WHAT IS KNOWN ALREADY: Alternative ovarian stimulation protocols have been introduced for women with breast cancer who opt for fertility preservation by means of banking of oocytes or embryos. How these ovarian stimulation protocols compare to standard ovarian stimulation in terms of COC yield is unknown. STUDY DESIGN, SIZE, DURATION: This multicentre, open-label randomized controlled superiority trial was carried out in 10 hospitals in the Netherlands and 1 hospital in Belgium between January 2014 and December 2018. We randomly assigned women with breast cancer, aged 18–43 years, who opted for banking of oocytes or embryos to one of three study arms; ovarian stimulation plus tamoxifen, ovarian stimulation plus letrozole or standard ovarian stimulation. Standard ovarian stimulation included GnRH antagonist, recombinant FSH and GnRH agonist trigger. Randomization was performed with a web-based system in a 1:1:1 ratio, stratified for oral contraception usage at start of ovarian stimulation, positive estrogen receptor (ER) status and positive lymph nodes. Patients and caregivers were not blinded to the assigned treatment. The primary outcome was number of COCs retrieved at follicle aspiration. PARTICIPANTS/MATERIALS, SETTING, METHODS: During the study period, 162 women were randomly assigned to one of three interventions. Fifty-four underwent ovarian stimulation plus tamoxifen, 53 ovarian stimulation plus letrozole and 55 standard ovarian stimulation. Analysis was according to intention-to-treat principle. MAIN RESULTS AND THE ROLE OF CHANCE: No differences among groups were observed in the mean (±SD) number of COCs retrieved: 12.5 (10.4) after ovarian stimulation plus tamoxifen, 14.2 (9.4) after ovarian stimulation plus letrozole and 13.6 (11.6) after standard ovarian stimulation (mean difference −1.13, 95% CI −5.70 to 3.43 for tamoxifen versus standard ovarian stimulation and 0.58, 95% CI −4.03 to 5.20 for letrozole versus standard ovarian stimulation). After adjusting for oral contraception usage at the start of ovarian stimulation, positive ER status and positive lymph nodes, the mean difference was −1.11 (95% CI −5.58 to 3.35) after ovarian stimulation plus tamoxifen versus standard ovarian stimulation and 0.30 (95% CI −4.19 to 4.78) after ovarian stimulation plus letrozole versus standard ovarian stimulation. There were also no differences in the number of oocytes or embryos banked. There was one serious adverse event after standard ovarian stimulation: one woman was admitted to the hospital because of ovarian hyperstimulation syndrome. LIMITATIONS, REASONS FOR CAUTION: The available literature on which we based our hypothesis, power analysis and sample size calculation was scarce and studies were of low quality. Our study did not have sufficient power to perform subgroup analysis on follicular, luteal or random start of ovarian stimulation. WIDER IMPLICATIONS OF THE FINDINGS: Our study showed that adding tamoxifen or letrozole to a standard ovarian stimulation protocol in women with breast cancer does not impact the effectiveness of fertility preservation and paves the way for high-quality long-term follow-up on breast cancer treatment outcomes and women's future pregnancy outcomes. Our study also highlights the need for high-quality studies for all women opting for fertility preservation, as alternative ovarian stimulation protocols have been introduced to clinical practice without proper evidence. STUDY FUNDING/COMPETING INTEREST(S): The study was supported by a grant (2011.WO23.C129) of 'Stichting Pink Ribbon', a breast cancer fundraising charity organization in the Netherlands. M.G., C.B.L. and R.S. declared that the Center for Reproductive Medicine, Amsterdam UMC (location VUMC) has received unconditional research and educational grants from Guerbet, Merck and Ferring, not related to the presented work. C.B.L. declared a speakers fee for Inmed and Yingming. S.C.L. reports grants and non-financial support from Agendia, grants, non-financial support and other from AstraZeneca, grants from Eurocept-pharmaceuticals, grants and non-financial support from Genentech/Roche and Novartis, grants from Pfizer, grants and non-financial support from Tesaro and Immunomedics, other from Cergentis, IBM, Bayer, and Daiichi-Sankyo, outside the submitted work; In addition, S.C.L. has a patent UN23A01/P-EP pending that is unrelated to the present work. J.M.J.S. reported payments and travel grants from Merck and Ferring. C.C.M.B. reports her role as unpaid president of the National guideline committee on Fertility Preservation in women with cancer. K.F. received unrestricted grants from Merck Serono, Good Life and Ferring not related to present work. K.F. declared paid lectures for Ferring. D.S. declared former employment from Merck Sharp & Dohme (MSD). K.F. declared paid lectures for Ferring. D.S. reports grants from MSD, Gedeon Richter and Ferring paid to his institution; consulting fee payments from MSD and Merck Serono paid to his institution; speaker honoraria from MSD, Gedeon Richter, Ferring Pharmaceuticals and Merck Serono paid to his institution. D.S. has also received travel and meeting support from MSD, Gedeon Richter, Ferring Pharmaceuticals and Merck Serono. No payments are related to present work. TRIAL REGISTRATION NUMBER: NTR4108. TRIAL REGISTRATION DATE: 6 August 2013. DATE OF FIRST PATIENT'S ENROLMENT: 30 January 2014.